Surface chemistry effects on work function, ionization potential and electronic affinity of Si(100), Ge(100) surfaces and SiGe heterostructures. Issue 44 (9th November 2020) - Marri, Ivan; Amato, Michele; Bertocchi, Matteo; Ferretti, Andrea; Varsano, Daniele; Ossicini, Stefano
Abstract : Surface chemistry effects are calculated within the many body perturbation theory for Si(100), Ge(100) and SiGe surfaces. Abstract : We combine density functional theory and many body perturbation theory to investigate the electronic properties of Si(100) and Ge(100) surfaces terminated with halogen atoms (–I, –Br, –Cl, –F) and other chemical functionalizations (–H, –OH, –CH3 ) addressing the absolute values of their work function, electronic affinity and ionization potential. Our results point out that electronic properties of functionalized surfaces strongly depend on the chemisorbed species and much less on the surface crystal orientation. The presence of halogens at the surface always leads to an increment of the work function, ionization potential and electronic affinity with respect to fully hydrogenated surfaces. On the contrary, the presence of polar –OH and –CH3 groups at the surface leads to a reduction of the aforementioned quantities with respect to the H-terminated system. Starting from the work functions calculated for the Si and Ge passivated surfaces, we apply a simple model to estimate the properties of functionalized SiGe surfaces. The possibility of modulating the work function by changing the chemisorbed species and composition is predicted. The effects induced by different terminations on the band energy line-up profile of SiGe surfaces are then analyzed. Interestingly, our calculations predict a type-II band offset for the H-terminated systems and a type-I band offset for the other cases.